Pseudochylopneumothorax: A rare presentation of reactivation of tuberculosis - Muzafar Ahmed Naik (The Journal of Association of Chest Physicians, 2014)
A 70-year-old male with past history of treated pulmonary tuberculosis presented with clinical, radiological, and laboratory features suggestive of pseudochylopneumothorax and bronchopleural fistula. Acid-fast bacilli (AFB) staining and AFB culture of pleural fluid was positive. Pseudochylothorax is a rare sterile complication of long standing tubercular effusion. Pseudochylothorax in itself can get complicated by reactivation of tuberculosis and bronchopleural fistula. The occurrence of pseudochylopneumothorax due to bronchopleural fistula as in our case is a rare manifestation of reactivation tuberculosis.